KOMPARASI KEPEMIMPINAN UMAR BIN ABDUL AZIZ DENGAN KEPALA SEKOLAH - Muhammad Syarif Mujahid; Muhammad Zainal Abidin (Qiro'ah : Jurnal Pendidikan Agama Islam, 2024)
This article examines the role of the model leader represented by Khalifah Umar bin Abdul Aziz in the context of school principal leadership. The caliph who was famous for his spiritual leadership which was consistent with the teachings of the Prophet Muhammad, Umar bin Abdul Aziz showed significant success in running the government even though his leadership period was not very long. This research compares the leadership values ​​contained in the Book Al Khalifatu Ar Rasyid Wal Mushlihu Al Kabir with the professionalism standards of school principals regulated in Minister of Education and Culture Regulation No. 40 of 2021. Qualitative methods were used in this research with a focus on library research. Primary data was obtained from a book written by DR. Ali Muhammad Ash-Shallabi about Umar bin Abdul Aziz, while secondary data comes from other literature relevant to the title of this research. The analysis technique used is content analysis, where the researcher compares and connects ongoing studies with this article. It is hoped that the results of this research will provide deeper insight into the potential for applying classical leadership values ​​in the context of modern education, as well as contributing to the development of more effective and efficient school principal leadership practices.